2011
DOI: 10.1007/s10528-011-9426-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Structure and Variation of Van Cats

Abstract: To determine the genetic structure and variation of Van cats and some other cats, seven enzyme loci were examined using horizontal starch gel electrophoresis. ME bands were observed for the first time in cats. For the enzyme loci CA ( 1 ), SOD, GPI, and GOT, neither the individual Van cats nor the specimens of other cat species exhibited any variation. These enzymes presented identical bands, all of which were homozygous. With respect to the PGD, ME, and ESD loci, however, genetic variation was observed in all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Another study showed Turkish Angora, Turkish Van and Persian differed from Siamese and Bombay cats. This study also indicated that Turkish Angora and Van cats had the PGD, ME and ESD loci but, unlike some other cat breeds, did not have enzyme loci CA 1, SOD, GPI and GOT [20]. An academic study investigated the genetic structure of various cat breeds through the use of microsatellites.…”
Section: Overviewmentioning
confidence: 85%
“…Another study showed Turkish Angora, Turkish Van and Persian differed from Siamese and Bombay cats. This study also indicated that Turkish Angora and Van cats had the PGD, ME and ESD loci but, unlike some other cat breeds, did not have enzyme loci CA 1, SOD, GPI and GOT [20]. An academic study investigated the genetic structure of various cat breeds through the use of microsatellites.…”
Section: Overviewmentioning
confidence: 85%